DC/DC converter design for PV for a DC micro grid - Huang, Wei Wei (2015)
Increase of DC-compatible loads, popularization of renewable distributed generations (DGs) and development of power electronic converters have boosted the applications of DC microgrid in household level. Proper control algorithms for autonomous operation of DC microgrid which coordinates the operation of energy storages, sources and loads become the key challenge. Comparing with centralized energy management system, distributed control eliminates communication link, thus system response speed and reliability could be enhanced. There are two different modes Double loop control for battery and MPPT control for PV. Bus voltage variation induced by power supply/demand difference activates operation mode change of system elements autonomously. When the demand more than supply the system will be in MPPT mode and the battery is in discharging condition. If the demand less than the supply it will switch to Double Loop control mode and the battery will be charged. A lab-scale DC microgrid with integration of modular solar Photovoltaic (PV) system, battery energy storage (BES) and DC loads was developed to verify the feasibility and effectiveness of proposed control algorithm.